SIFAT PENDIDIK DALAM AL QURAN: KAJIAN TAFSIR AL-AZHAR KARYA BUYA HAMKA - Sufyan, Sufyan; Darodjat, Darodjat (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2024)
Educators must have the ability to carry out their duties and responsibilities as educators, both in guiding and training students. With this ability, educators can better help students develop their intellectual, emotional, social and spiritual-moral aspects. An educator not only has extensive knowledge. More than that, they must have faith, have noble character, be earnest in carrying out their professional duties, and see their work as a mandate Allah gave them and carried out well. In the Islamic education system, educators are expected to have various characteristics and can be role models and positive influences on their students. This research is literature research with a qualitative approach. In this research, we discuss the characteristics of educators collected from the verses of the Koran by referring to the study of the interpretation of Al Azhar, from which verses are then selected appropriate to the theme being studied (characteristics of educators). This research concludes that educators must have patience, be gentle, teach knowledge, and fear Allah SWT